Implementasi QRIS dalam Meningkatkan Efisiensi Transaksi Mahasiswa di Era Ekonomi Digital (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
The development of the digital economy is driving a shift in payment systems from cash to non-cash, one of which is through the use of the Quick Response Code Indonesian Standard (QRIS). This study aims to analyze the implementation of QRIS in improving student transaction efficiency in the digital economy era and its implications for changes in transaction behavior. This study uses a descriptive qualitative approach with a case study method. Data were obtained through in-depth interviews and observations of six students who actively use QRIS in their daily transaction activities on campus. The results show that QRIS has been widely used by students because it is considered practical, fast, and secure. The use of QRIS can improve transaction efficiency, especially in terms of time, convenience, and security, and encourage the formation of a culture of non-cash transactions among students. However, the effectiveness of QRIS implementation still faces obstacles, such as internet network disruptions and limited digital wallet balances. This study concludes that QRIS plays an important role in supporting student transaction efficiency, but strengthening digital infrastructure and increasing digital financial literacy are needed to optimize its benefits in the digital economy era.